2020
DOI: 10.32890/jis.14.2018.7997
|View full text |Cite
|
Sign up to set email alerts
|

The Eastern Democratic Republic of Congo Recurring Conflict: Whose Conflict Transformation Responsibility?

Abstract: The recurring conflict in Eastern DRC has had devastating effects on civilians, mostly in Kivus. From the beginning of January 2002 till the end of May 2017, many conflict resolution efforts have been put together by regional and international communities. However, there has not been any sustainable mechanism to resolve the conflict. The situation regarding the security of Eastern Congo continues to be volatile. This paper seeks to identify the responsible party that would help mitigate the recurring conflict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The conflicts that emanate from the spread of SALW in Africa continues unabated. For instance, Maeresera, Rugeje & Zengeni (2018) suggested that SALW is the main factor in the defiant nature of Congo's armed conflict for many years, up to 2017. In another view, Mukhtar, Che Rose, Choy & Bibi-Farouk (2018) proposed that Boko Haram in Nigeria was able to terrorize the country that led to force migration, as a result of the use of IEDs and other SALW which they have acquired through the illicit route of transfer and marketing.…”
Section: Emergence Of Small Arms and Light Weapons (Salw) In Africamentioning
confidence: 99%
“…The conflicts that emanate from the spread of SALW in Africa continues unabated. For instance, Maeresera, Rugeje & Zengeni (2018) suggested that SALW is the main factor in the defiant nature of Congo's armed conflict for many years, up to 2017. In another view, Mukhtar, Che Rose, Choy & Bibi-Farouk (2018) proposed that Boko Haram in Nigeria was able to terrorize the country that led to force migration, as a result of the use of IEDs and other SALW which they have acquired through the illicit route of transfer and marketing.…”
Section: Emergence Of Small Arms and Light Weapons (Salw) In Africamentioning
confidence: 99%
“…After independence, neo-colonial predation under President Mobutu, who was installed by the West, was followed by long years of war at the turn of the millennium. The extreme cross-generational trauma of Congolese civilians resulting from these historical and more recent mass atrocities leaves scars that can produce recurring cycles of attack and revenge (Maeresera et al., 2018; Mels et al., 2010). As Mobutu’s regime collapsed, the toxic realities of the Rwandan genocide, inspired by racial thinking, spilled over into Zaire, intensifying ‘race’ as a vector of violence and conflict in Eastern Congo end sentence at Congo.…”
Section: Introductionmentioning
confidence: 99%